Mechanism of propaganda in the Boletín Titikaka - Coca Vargas, César (2020)
In contrast to the research on the Boletín Titikaka (1926-1930), I want to think about the mechanisms of propaganda executed by its leader, Gamaliel Churata, to understand the ultimate nature of the orkopata magazine. In this way, I aim to demonstrate that the Boletín Titikaka had as its main purpose the visibility of its own project, which meant the interested utilization of the Andean reference. For this reason, I affirm that the indigenous representation, which they constantly draw on, was subordinated to an agenda that focused on the Orkopata group. My reflections will influence the capital importance that the poetry book Ande (1926) accomplished for the realization of the objectives of Churata. Paying attention to the Ande – Boletín Titikaka relationship, I will use two images of ambivalence, paskana and erysipelas, to understand the notions of representation, self-representation, participation and agency.